Anomalies of geomagnetic field due to a vertical prolate rotational ellipsoid - HVOŽDARA, Milan; VOZÁR, Ján (Contributions to Geophysics and Geodesy, 2010)
We present an exact analytical solution of the forward magnetometric problem for the perturbing body having the shape of the rotational prolate ellipsoid with the longer axis oriented vertically to the surface of the earth. The anomaly of ΔZ and ΔT is calculated for the network of points in the plane z = const above the ellipsoid, as well as for the points on the surfaces of the volcanic hill: i) the cut cone, ii) the smooth shape given by the rotation of the Gaussian curve. Theoretical results can be useful for the interpretation of land or aeromagnetic survey in the volcanic areas.